2015
DOI: 10.7314/apjcp.2015.16.4.1565
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to Cervical Screening among Pacific Women in a New Zealand Urban Population

Abstract: Asian Pac J Cancer Prev, 16 (4), [1565][1566][1567][1568][1569][1570] IntroductionThe Pacific population generally in New Zealand grew from the recent immigrant community of the 1940's of just over 2000 to over a quarter of a million in 2013 and now make up seven per cent of the total population and the fourth largest ethnic group. The leading three ethnic groups being Europeans (74%), Maori (15%) and Asian (12%) whose population size almost doubling between 2001 and 2013. The Pacific population in New Zealan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(21 citation statements)
references
References 13 publications
1
20
0
Order By: Relevance
“…Lastly, inconvenient screening services, in terms of timing and location, also posed a major barrier for the rural women in our study. This applies to those who must relocate for paid work and those whose family care duties leave little time for health screening; findings also seen in a wide range of other settings 33 47 48. Delivering services at times, even holiday times, and in places where women already congregate, perhaps through mobile services, may help overcome this barrier in China, and elsewhere 46…”
Section: Discussionmentioning
confidence: 99%
“…Lastly, inconvenient screening services, in terms of timing and location, also posed a major barrier for the rural women in our study. This applies to those who must relocate for paid work and those whose family care duties leave little time for health screening; findings also seen in a wide range of other settings 33 47 48. Delivering services at times, even holiday times, and in places where women already congregate, perhaps through mobile services, may help overcome this barrier in China, and elsewhere 46…”
Section: Discussionmentioning
confidence: 99%
“…Another similar study carried out in New zealand reported the cost of screening, awareness and individual sense towards self and screening affect cervical screening attendance (Foliaki and Matheson, 2015). It is clear that screening participation is low in our society.…”
Section: Discussionmentioning
confidence: 90%
“…Our review identified many barriers to CALD populations obtaining health care. Table 1 shows the range of barriers identified in references from New Zealand (with respect to Pacific peoples), [14][15][16][17][18][19] Australia [20][21][22] and the USA. 23,24 Strategies to overcome these barriers One strategy to overcome the health-care barriers for CALD populations has been to deploy specific health workers who are members of CALD communities to assist with navigating the system.…”
Section: Barriers To Health Carementioning
confidence: 99%
“…The design of the health system, including opening hours and location of facilities 14,[16][17][18]23 The complexity of health systems 14,24 The lack of health-care providers from CALD communities 16,18,22,24 Attitudes of health-care providers [15][16][17][18] Cost of services [16][17][18][19][20]23 Physical access to services or transport, relating to geographical location of services 14,17,19,22 Language, including English-language ability and knowledge of medical terminology 14,15,[17][18][19][20][21][22] Cultural barriers, including lifestyle, fear of discrimination, different perceptions of health 14,16,[18][19][20][21][22] Health literacy, including unfamiliarity with health systems and lack of information 17,[20][21][22][23][24] Lack of trust…”
Section: Terminologymentioning
confidence: 99%